Just a Joke? Audience Interpretations of Sexist Humor in Ludruk Performances - Rahmiati, Dyan; Maryani, Eni; Dida, Susanne; Hadisiwi, Purwanti (Institut Komunikasi dan Bisnis LSPR, 2024)
Sexist humor has emerged as a controversial issue at the intersection of gender, communication, and traditional entertainment. While often dismissed as harmless amusement, such humor can reinforce gender stereotypes and normalize social bias, particularly in local performance contexts. This study explores audience interpretations of sexist humor in ‘Ludruk’, a traditional Indonesian theatre from known for comedy content that incorporates gendered themes. Adopting an Interpretive Phenomenological Analysis (IPA) approach. the research involves six participants who regularly attended Ludruk performances. Through in-depth interviews conducted in the local Javanese dialect, the study examined participants' interpretations, emotional responses, and the cultural and social context shaping their perspective. The findings indicate that participants generally view sexist humor as mere entertainment, rarely considering its broader societal implications. Male participants emphasize humor delivery and comedic timing, while female participants often rationalize their laughter as a means of social conformity, avoiding being perceived as overly critical. The immersive performance environment of Ludruk, combined with its improvisational and participatory nature, fosters social bonds among audience members and between performers and spectators. These cultural dynamics, deeply rooted in Javanese social norms and expectations of group harmony, contributed significantly to the acceptance and normalization of sexist content. This study highlights how humor operates within specific cultural contexts and how social laughter functions as a mechanism of social cohesion, even when problematic. It underscores the importance of critically examining traditional entertainment practices that may perpetuate gendered social norms under the guise of innocuous fun.